Conventional and microwave prompted synthesis of aryl(alkyl)azole oximes, 1H-NMR spectroscopic determination of E/Z isomer ratio and HOMO-LUMO analysis - Bozbey, Irem; Uslu, Harun; Turkmenoglu, Burcin; Ozdemir, Zeynep; Karakurt, Arzu; Levent, Serkan (Elsevier, 2022)
In this study, 12 oxime derivatives were synthesized by using with conventional method and microwave irradiation method. It was aimed to compare the effectiveness of the conventional method and microwave method. Their yields were determined for both methods, and the yields increased when the microwave method was used. The compounds which have oxime show geometric isomerism because they have carbon-nitrogen double bonds. Therefore, we have also aimed to evaluate their E/Z isomer ratios in this study. While the synthesized pyrazole derivative compounds were mostly obtained in Z isomer in both synthesis methods, it was observed that some of the title compounds were almost completely obtained as E isomers when the conventional synthesis method was used in the synthesized imidazole derivative compounds. The structures of synthesized compounds were confirmed by IR, H-1-NMR, C-13-NMR and HRMS spectra. Additionally, in this study, the HOMO-LUMO energies and thermodynamic properties of the E/Z isomers of 12 oxime derivatives were performed using the 6-31 * G basis set and the Density Functional Theory (DFT) calculation using the B3LYP method three different environments (water, ethanol, vacuum). In addition, geometric parameters such as chemical hardness (eta), chemical potential (mu), electrophilicity index (omega), chemical softness (sigma) were calculated depending on the calculated HOMO-LUMO energies. (C) 2021 Elsevier B.V. All rights reserved.
Keywords: Azole derivatives; Oxime; Microwave; E/Z isomers; DFT